Mengkaji Kecerdasan Emosional dan Regulasi Emosi pada Mahasiswa yang Bekerja: Wahyu Aulizalsini, Rheina Rizky Rizal - Aulizalsini, Wahyu; Rizky Rizal , Rheina (SOCIAL PHILANTHROPIC, 2024)
Students who carry out two roles at once as workers often have to face double challenges. The pressure that comes from college and work loads often makes students deal with academic stress. The ability to manage emotions is needed in facing both roles at once for working students. This research aims to explore the relationship between emotional intelligence and emotional regulation in working students. The method used in this research is a quantitative method with a correlation type approach with a population of Bhayangkara University students working with a sample size of 134 (N=134). The statistical analysis used uses a parametric test using the Pearson Product Moment. The results of the data analysis test were obtained with a significance level of 0.000 (p < 0.05) with a coefficient value of 0.929, which means the two variables have a very high relationship